Leptin: a biomarker of fetal adiposity and insulin resistance. (18th April 2012) - Walsh, JM; Mahony, RM; Foley, ME; McAuliffe, FM
Abstract : Background: Evidence is accumulating that leptin can be regarded as a biomarker of fetal adiposity. We sought to clarify the relationship between maternal and fetal leptin, insulin resistance and both maternal and fetal adiposity in a healthy, euglycemic population. Methods: This is a prospective study of 574 mother and infant pairs. Women were recruited at first antenatal consultation. At this visit maternal weight, height and arm circumference (a marker of maternal adiposity) were recorded. Maternal leptin, glucose and insulin were measured in early pregnancy and again at 28 weeks and the HOMA index calculated. At 34 weeks, ultrasound assessed fetal anthropometry including anterior abdominal wall width (AAW), a marker of fetal adiposity. At delivery birthweight and cord blood c-peptide and leptin were recorded. Results: There was a correlation between maternal and fetal leptin concentrations and both maternal BMI ((r=0.52 in early pregnancy, r=0.42 at 28 weeks, r=0.16 in cord blood, p<0.001 for all) and maternal adiposity (r=0.46 in early pregnancy, r=0.34 at 28 weeks and r=0.215 in cord blood, p<0.05 for all). Those with higher HOMA indices at each timepoint had higher leptin concentrations. Fetal, not maternal, leptin was significantly related to AAW at 34 weeks (r=0.14, p=0.013). Conclusion: Our findings confirm the significant influence of leptin on fetal growth. Leptin was associated not only with the deposition of fat in utero but also with maternal and fetal insulin resistance. These findings suggest that leptin is a biomarker for fetal adiposity, and may have a role in the fetal programming of childhood obesity.